2022
DOI: 10.1055/s-0042-1757200
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and the Risk of Venous Thromboembolism after Major Lower Limb Orthopaedic Surgery: A Literature Review

Abstract: The risk of venous thromboembolism following total joint arthroplasty is significantly greater than those of other types of elective orthopaedic procedures. This risk is increased in obesity due to the associated prothrombotic physiological and hematological changes that predispose to embolic events. The prevalence of obesity is increasing in the aging population, which contributes to a further increase in the risk of postoperative thrombosis in the older patients. There is a lack of clear evidence regarding d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 92 publications
0
10
0
Order By: Relevance
“…It has no significant difference in the incidence of SVT among the two groups ( p = 0.489, Table 2). However, the guideline was published by the American Academy of Orthopedic Surgeons, which suggests using pharmacologic agents and/or mechanical compressive devices to prevent VTE in patients undergoing TKA as a moderate recommendation 7,8 . The American College of Chest Physicians recommends using one of the following for 10 to 35 days 9,10 .…”
Section: Discussionmentioning
confidence: 99%
“…It has no significant difference in the incidence of SVT among the two groups ( p = 0.489, Table 2). However, the guideline was published by the American Academy of Orthopedic Surgeons, which suggests using pharmacologic agents and/or mechanical compressive devices to prevent VTE in patients undergoing TKA as a moderate recommendation 7,8 . The American College of Chest Physicians recommends using one of the following for 10 to 35 days 9,10 .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, various studies have shown the impact of obesity on the risk of venous thromboembolism (VTE). 3,4 While obesity per se is a risk, the added impact of prothrombotic genotypes has been reported from the Tromsø Study (1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012) and the Trøndelag Health Study (HUNT) (1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008). 5 In this issue of Thrombosis & Haemostasis, Frischmuth et al 6 report from Tromsø, Norway, a survey of 36,341 participants.…”
mentioning
confidence: 99%
“…Indeed, various studies have shown the impact of obesity on the risk of venous thromboembolism (VTE). 3 4 While obesity per se is a risk, the added impact of prothrombotic genotypes has been reported from the Tromsø Study (1994–2012) and the Trøndelag Health Study (HUNT) (1995–2008). 5 In this issue of Thrombosis & Haemostasis , Frischmuth et al 6 report from Tromsø, Norway, a survey of 36,341 participants.…”
mentioning
confidence: 99%
“…1 Lifetime estimated risk of VTE in the United States is 8.1%, notably higher in black persons. Other important risk factors for developing VTE include obesity, 2 postsurgical populations, 3 recently hospitalized, cancer, 4 and those with sleep apnea. 5 Recent focus has included the associations of VTE to pregnancy and family history in women of childbearing age 6 7 as well as those with assisted reproductive technology.…”
mentioning
confidence: 99%